Effects of different cooking methods on the antioxidant capacity and flavonoid, organic acid and mineral contents of Galega Kale (Brassica oleracea var. acephala cv. Galega). (17th February 2019) - Armesto, Jorge; Gómez-Limia, Lucía; Carballo, Javier; Martínez, Sidonia
Abstract: Brassica spp. are good sources of bioactive substances, which are known to have beneficial health effects. The objective of this work was to evaluate the effect of different cooking methods (boiling, steaming, microwaving, pressure cooking and vacuum cooking) on the antioxidant capacity and on the flavonoid, organic acid and mineral contents of Galega kale. Results indicate that this vegetable has a high antioxidant capacity and high contents of total flavonoids, organic acids, and minerals such as potassium and calcium. All of the cooking methods yielded losses of antioxidant capacity and of total flavonoids, organic acids and minerals, relative to the contents in fresh kale. Steaming proved to be the best method of preserving the antioxidant capacity and bioactive compounds. Although cooking did not cause large losses of oxalic acid, the resulting oxalate:calcium ratio was rather low (<2). The present data demonstrate that the different cooking methods have different effects on the bioactive compounds in kale, and that it is important the optimisation of such methods in order to minimise losses of the nutritional properties. Abstract :